Probing the biological toxicity of pyrene to the earthworm Eisenia fetida and the toxicity pathways of oxidative damage: A systematic study at the animal and molecular levels. (15th November 2021) - Sun, Ning; Liu, Qiang; Wang, Jinhu; He, Falin; Jing, Mingyang; Chu, Shanshan; Zong, Wansong; Liu, Rutao; Gao, Canzhu
Abstract: Pyrene (Pyr), a widely used tetracyclic aromatic hydrocarbon, enters soil in large quantities and causes environmental pollution due to its production and mining. In order to systematically study the biotoxicity of pyrene to model organisms Eisenia fetida in soil, experiments were carried out from four dimensions: animal, tissue, cell and molecule. Experimental results proved that the mortality rate increased with increasing concentration and time of exposure to pyrene, while the mean body weight and spawning rate decreased. Meanwhile, when the pyrene concentration reached 900 mg/kg, the seminal vesicle and longitudinal muscle of the earthworm showed obvious atrophy. Experimental results at the cellular level showed that pyrene induced cell membrane damage and Ca 2+ influx triggered mitochondrial membrane depolarization and a surge in ROS levels. Oxidative stress causes damage to proteins and lipids and DNA inside cells. When the mortality rate was 91.67 %, the Olive Tail Movement (OTM) of the comet experiment reached 15. The results of molecular level tests showed that pyrene inhibited the activity of Cu/Zn-superoxide dismutase (Cu/Zn-SOD) mainly by changing the microenvironment and secondary structure of amino acid Tyr 108. The weakened function of direct antioxidant enzymes may be the root cause of the excessive increase of reactive oxygen species (ROS) in cells. The systematic approach used in this study enriches the network of toxic pathways in toxicological studies, and basic data on the biological toxicity of pyrene can provide support for future soil contamination detection. Graphical abstract: Image 1 Highlights: The ecological toxicity of pyrene to earthworms was studied systematically. The toxic pathway of oxidative stress was explored at the cellular level. The interaction between pyrene and Cu/Zn-SOD was linked to cytotoxicity.